PROMOTING ORAL COMMUNICATION THROUGH READING INTEGRATION (Scientific journal of the Fergana State University, 2024)
This article explores the hypothesis that incorporating reading materials in language classes can enhance students' oral communication skills. It must be mentioned about the importance of oral communication in language learning and the challenges that students often face in developing this skill. It introduces the hypothesis that integrating reading materials into language classes can help address these challenges and improve students' oral communication abilities. Additionally, it reviews existing literature on the topic, highlighting studies that have found a positive correlation between reading and oral communication skills.